An analysis of the primary care systems of Ireland and Northern Ireland - Sheelah Connolly; Aofe Brick; Ciarán J. O'Neill; Michael O'Callaghan (The Economic and Social Research Institute (ESRI), 2022)
Recent reform proposals in the healthcare systems of Ireland and Northern Ireland have highlighted the need to improve population health and to deliver more care in the community. There are significant variations between the two healthcare systems, providing an opportunity to examine how different approaches and policies impact on a range of outcomes. The aim of this research study is to analyse the primary care systems of Ireland and Northern Ireland. In doing so, it seeks to inform the reform proposals for both systems. The analysis will focus on primary care due to the key differences between the primary care systems of Ireland and Northern Ireland, including the higher prevalence of user charges in the Irish healthcare system.
Keywords: 330; Gesundheitswesen; Vergleich; Irland; Nordirland